Low shrinkage, mechanically strong polymethylacrylimide aerogels with open-cell structure prepared by freeze-drying. (6th April 2022) - Zhang, Jing; Zhang, Hongli; Yan, Tinghui; Fang, Ye; Huang, Yuzhong; Tang, Jijun; He, Mingyang
Abstract: Low shrinkage, open-cell structure, and mechanically-strong polymethylacrylimide (PMI) aerogels were synthesized using a freezing-drying process. Specifically, methacrylonitrile (MAN) and methacrylic acid (MAA) were used as the comonomers to synthesis the copolymer. PMI aerogels after heat treatment presented the lowest shrinkage of 10.5%. The fabricated aerogels exhibited a network-like structure with the minimum measured porosity of 89%. Increasing the copolymer solid contents resulted in a better compression property. The maximum stress of the PMI aerogels at 50% strain can reach 0.256 MPa. The fabricated aerogels presented low thermal conductivity and density, as low as 43 mW/mK and 0.050 g/cm 3, respectively. Graphical abstract: Image 1 Highlights: Expand the product form of polymethylacrylimide materials. Determine the chemical structure of aerogels by FTIR and TGA. Study on solid content to structure and properties of polymethylacrylimide aerogels.